REPRESENTASI MITOLOGI BUDAYA DALAM NOVEL "TUTUR DEDES DOA DAN KUTUKAN" KARYA AMALIA YUNUS - Suciati, Voni; Syam, Christanto; Seli, Sesillia (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
This study aims to determine the representation, function of cultural mythology in the novel Said Dedes Prayers and Curses by Amalia Yunus, and describes the implementation plan for teaching literature in schools. This research method is a descriptive method with a qualitative research form. The data source is Novel Said Dedes Prayers and Curses Amalia Yunus's work and data on quotations of words, phrases and sentences containing cultural mythology in the novel. The results of this study show a representation of the geographical level, namely around the house, Mount Kawi forest, Mandala, Mount Kampud, State Corner, Temple, Trembesi forest. At the techno-economic level, people are looking for dukun beranak, traders, mirror experts, breeders, fishermen, farmers, and keris experts. The sociological level is that of Buddhist priests, solitary warriors, rulers of the kingdom of Kediri, rulers of tumapel, the maha bhiksu, royal bodyguards, kings and queens, patih courtiers, brahmins, future kings and queens, commoners, concubines, commoners who become kings. The cosmological level is the myth of pamali, baby placenta, smelling of roasted tubers, prenjak bird, about the rooster crowing at midnight, about some bad omens, fasting ceremony, vaginal area that glows blue, Rawarontek ajian, and trembesi forest, it was found that the function of cultural mythology is to give power to humans to take part in natural processes, provide world knowledge, a system for conveying messages, and as a means of education, as well as plans for implementing literary learning in schools.